2012
DOI: 10.1002/cite.201200143
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess Development in Single‐Use Systems for Heterotrophic Marine Microalgae

Abstract: The utilization of single‐use systems is more and more common in upstream cultivation in biotechnological processes. The advantages of single‐use bioreactors for the cultivation of the heterotrophic microalgae Crypthecodinium cohnii serves as an example for the feasibility of polymer based orbital shaken systems for shear‐sensitive microorganisms with a high oxygen demand. Experiments in the shake flask scale indicate the advantage of tubes like the TubeSpin Bioreactor 600 in comparison to standard Erlenmeyer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…From the bioprocess engineering point of view, PFCs are recognized as the most flexible liquid carriers/scavengers of gaseous compounds (O 2 and CO 2 , mainly) and were successfully applied in culture systems of various types of cells, i.e. microorganisms such as bacteria (Pilarek et al 2011;2013a), yeast (Pilarek et al 2006), fungi (Elibol and Ozer 2000) and microalgae (Hillig et al 2013(Hillig et al , 2014, animal (Shiba et al 1998;Rappaport 2003;Pilarek et al 2013bPilarek et al , 2014Douglas et al 2014) as well as plant cells (Wardrop et al 1996;Lowe et al 2003;Davey et al 2005;Pilarek and Szewczyk 2008;Sykłowska-Baranek et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…From the bioprocess engineering point of view, PFCs are recognized as the most flexible liquid carriers/scavengers of gaseous compounds (O 2 and CO 2 , mainly) and were successfully applied in culture systems of various types of cells, i.e. microorganisms such as bacteria (Pilarek et al 2011;2013a), yeast (Pilarek et al 2006), fungi (Elibol and Ozer 2000) and microalgae (Hillig et al 2013(Hillig et al , 2014, animal (Shiba et al 1998;Rappaport 2003;Pilarek et al 2013bPilarek et al , 2014Douglas et al 2014) as well as plant cells (Wardrop et al 1996;Lowe et al 2003;Davey et al 2005;Pilarek and Szewczyk 2008;Sykłowska-Baranek et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…insoluble fraction of not-correctly folded protein molecules) achieved in milliliter-scale of dispersed PFD containing cultures of E. coli has been reported by Pilarek et al (2011). The same group has also informed of a 25 % increase in plasmid DNA yield biosynthesised in E. coli cells cultured in PFDsupported microliter-scale system (Grunzel et al, 2014;Pilarek et al, 2013). Such a huge range of culture volumes (from 10 ) which has been reviewed in Table 4 (as well as discussed above) clearly indicates that perfluorinated oxygen carriers are very flexible bioengineering tools for gas transfer intensification in scaling-up or scaling-down of bioprocesses.…”
Section: Pfc-mediated Oxygen Transfer Intensificationmentioning
confidence: 80%
“…microorganisms, e.g. bacteria (Pilarek et al, 2011;Pilarek et al, 2013a), yeast (Pilarek and Szewczyk, 2008;Pilarek et al, 2006), fungi (Elibol, 2001) or microalgae (Hillig et al, 2013;Hillig et al, 2014), or plant cells (Davey et al 2005;Pilarek and Szewczyk 2008;Sykłowska-Baranek et al 2014) as wells as animal (Douglas et al 2014;Pilarek et al, 2013b;Pilarek et al, 2014;Rappaport, 2003;Shiba et al, 1998) to successfully obtain higher cell densities or to identify positive influence on metabolite excretion due to enhanced the mass transfer effects in culture systems, mainly.…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 content was determined with an optical sensor (PreSens, Regensburg, Germany). Surprisingly, the positive influence of oxygenated PFD on DHA production, which was described in [88], was not visible when only a few samples were taken manually within a very short time (Fig. 5).…”
Section: Cultivation In Deep-well Platesmentioning
confidence: 80%
“…Nile Red staining intensity was highest at 180 rpm, and the distribution of the cells was narrow compared to results obtained at 315 rpm (Figure 8). This finding indicated that shear stress had a negative influence on the DHA content of the cells [88]. Hence, although a higher power input is achieved, which increases the gas transfer rate, the high shear forces act counter to the goal of increasing the product yield.…”
Section: Microalgae Cultivation In Ultra Yield Flasksmentioning
confidence: 94%